Influence of thickness of SiO2 layer on the performance of SINW sensors. (29th December 2020) - Wang, Hui; Chen, Shixing; Wang, Yuelin; Li, Tie
Abstract: Silicon nanowire devices employed traditional MEMS technology has the advantages of low cost and easy to batch fabricated, which can be applied for high‐sensitivity biological and chemical species detection. In the preparation process, the device performance would be greatly influenced by the BOE corrosion process of silicon oxide outside silicon nanowires, which will define the performance of devices in subsequent test. In this paper, pH solution test was used to characterize the response sensitivity of silicon nanowires in different etching times, with the help of SEM and I – V characteristics before and after corrosion, it can be found that the thickness of silicon oxide layer enclosed nanowires was gradually reduced until completely etched in about five minutes to expose the silicon nanowires, which revealed that the silicon nanowires could start to sense and respond to external stimulus only when the silicon oxide was very thin even disappeared. The effect of corrosion could be equivalent to the influence of silicon oxide thickness on device performance. It provides an effective way to control the fabrication process of high performance devices.